A Phase 2, Randomized, Double-blind, Placebo-Controlled Trial of Presatovir for the Treatment of Respiratory Syncytial Virus Upper Respiratory Tract Infection in Hematopoietic-Cell Transplant Recipients. (3rd December 2019) - Chemaly, Roy F; Dadwal, Sanjeet S; Bergeron, Anne; Ljungman, Per; Kim, Yae-Jean; Cheng, Guang-Shing; Pipavath, Sudhakar N; Limaye, Ajit P; Blanchard, Elodie; Winston, Drew J; Stiff, Patrick J; Zuckerman, Tsila; et al.
Abstract: Background: Hematopoietic-cell transplant (HCT) recipients are at risk for severe respiratory syncytial virus (RSV) infection. We evaluated the RSV fusion inhibitor presatovir in a randomized, double-blind, Phase II trial in HCT recipients with RSV upper respiratory tract infections. Methods: Patients were stratified by lymphopenia (<200/µL) and ribavirin use; were randomized, stratified by lymphopenia (<200/μL) and ribavirin use, to receive oral presatovir at 200 mg or a placebo on Days 1, 5, 9, 13, and 17, and were followed through Day 28. The coprimary efficacy endpoints were the time-weighted average change in the nasal RSV viral load between Days 1 and 9 and the proportion of patients developing lower respiratory tract complications (LRTCs) through Day 28. Results: From 23 January 2015 to 16 June 2017, 189 patients were randomly assigned to treatment (96 to presatovir and 93 to the placebo). Presatovir treatment, compared with the placebo treatment, did not significantly affect (prespecified α = 0.01) a time-weighted average decline in the RSV viral load from Day 1 to 9 (treatment difference, −0.33 log10 copies/mL; 95% confidence interval [CI] −.64 to −.02 log10 copies/mL; P = .040) or the progression to LRTC (11.2% vs 19.5%, respectively; odds ratio, 0.50; 95% CI, .22–1.18; P = .11). In a post hoc analysis among patients with lymphopenia, presatovir decreased LRTC development by Day 28 (2/15 [13.3%] vs 9/14 [64.3%], respectively; P = .008), compared with the placebo. Adverse events were similar for patients receiving presatovir and the placebo. Conclusions: Presatovir had a favorable safety profile in adult HCT recipients with RSV but did not achieve the coprimary endpoints. Exploratory analyses suggest an antiviral effect among patients with lymphopenia. Clinical Trials Registration: NCT02254408; EUDRA-CT#2014-002474-36. Abstract : Presatovir treatment was safe but did not improve viral or clinical outcomes in hematopoietic-cell transplant recipients with respiratory syncytial virus upper respiratory tract infections. Exploratory analyses suggest clinical benefit in hematopoietic-cell transplant patients with lymphopenia at presentation.